Optimización de los protocolos de congelamiento de semen equino - Caldevilla, Mariana (2025)
Sperm cryopreservation represents a potential means to conserve a species' genetic resources. In equines, gamete cryopreservation allows the generation of genetic banks, maximizing the use of genetically superior stallions. Reproductive selection is not carried out in this species because the selection criteria is based on a specific genotype, defined by sporting, genealogical, aesthetic or conformation criteria. This has generated a high individual variability, typical of this species, in the response to cryopreservation. Despite a notable improvement in cryopreservation techniques over the last forty years, they have not yet been able to significantly increase pregnancy rates. Motility and fertility of frozen-thawed sperm differs greatly between stallions and even between ejaculates from the same stallion, with a prevalent decrease in sperm survival in all cases. A wide variety of preservation methods have been used to cryopreserve equine semen, however a relatively high percentage of stallions produce sperm that do not survive the cryopreservation process. Thus, a significant part of the stallion population is excluded from semen freezing programs, due in part to the poor results in postthaw semen quality and also to the low pregnancy rates obtained. Because of this, the objective of this thesis was to optimize equine semen cryopreservation protocols. It has been reported that an excessive acummulation of reactive oxygen species (ROS or ERO) can damage the sperm plasma membrane and DNA and for this reason the addition of different antioxidants to semen cryopreservation extenders has been assayed over the years. Studies on equine sperm metabolism have also been carried out, observing that these cells depend mostly on oxidative phosphorylation and pyruvate is the main metabolic substrate in this case. For these reasons, the addition of pyruvate to semen extenders for room temperature preservation has shown good results, along with the addition of L-carnitine as a facilitator of the use of pyruvate by the sperm cells and taking advantage also of its antioxidant properties. Taking this into account, the addition of pyruvate and L-carnitine, either to the equine semen cryopreservation extender or postthaw, was tested in this thesis. On the other hand, egg yolk routinely used in various semen cryopreservation protocols in different species, presents certain limitations for its use. Among these limitations, the restrictions forcommercializing cryopreserved semen due to the risk of contamination are prominent. Due to this, it was decided to evaluate the efficacy of equine cryopreservation media without egg yolk, with the purpose of developing a safer and more standardized alternative. For this thesis, stallions of proved fertiliy, housed either at the Faculty of Veterinary Sciences of the University of Buenos Aires or at private establishments, were used. In all cases kinematic parameters were evaluated using a CASA system, viability and acrosome reaction using FITC-PNA/PI staining, membrane lipoperoxidation using the fluorescent probe BODIPY and DNA fragmentation using the halo technique. For each experiment, when the data showed a normal distribution, they were analyzed using an analysis of variance and those variables that did not have normal distribution were analyzed using Friedman?s test or the Kruskal Wallis test. Data are expressed as mean ± standard deviation and the level of significance was set at 5%. Regarding the results obtained adding 50 mM L-carinitine and 10 mM pyruvate either to the cryopreservation extender prior to freezing or after thawing, showed that these components were not harmful to spermatozoa. However, they did not exert the expected beneficial effect on equine sperm parameters, at least under the conditions evaluated in this thesis. Regarding the use of egg yolk-free extenders, the bovine commercial formulations: AndroMed®, OptiXcell® and BioXcell® were not effective for cryopreserving equine semen with either of the temperature descent curves used. As for the commercial equine cryopreservation extender, with the addition of 3% DMF it could be an alternative to replace the extenders with egg yolk. However, it is evident that more research is needed to increase the existing information on the damage induced by the freezing process on equine spermatozoa. This information would be useful to continue introducing improvements to the current cryopreservation protocols, especially with regard to increasing sperm survival upon thawing, as it would be highly beneficial for the reproductive management of breeding establishments.